2008
DOI: 10.1007/s00125-008-1241-3
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant of G6PC2 is associated with type 2 diabetes and fasting plasma glucose level in the Chinese population

Abstract: Aims/hypothesis Single nucleotide polymorphisms (SNPs) in G6PC2 have been reported to be associated with fasting plasma glucose level in several populations of European descent. However, whether G6PC2 variants have a similar effect in other ethnic groups is unknown. The aim of this study was to investigate the effect of common variants of G6PC2 on type 2 diabetes and related clinical features in a Chinese population. Methods We selected four SNPs, rs13387347, rs2232316, rs492594 and rs16856187, tagging all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
6
36
0
Order By: Relevance
“…Since GWAS data show that the rs560887-G allele is associated with elevated FBG (Bouatia-Naji et al 2008; Chen et al 2008), the combination of these splicing (Baerenwald et al 2013) and G6pc2 KO mouse (Pound et al 2013; Wang et al 2007) studies suggest that rs560887 is a potentially causative variant. The association between G6PC2 and FBG has been confirmed in multiple GWAS and in different populations (Bouatia-Naji, et al 2009; Dupuis, et al 2010; Hu, et al 2009; Hu, et al 2010; Prokopenko, et al 2008; Reiling, et al 2009; Tam, et al 2010; Wang, et al 2013). …”
Section: Introductionmentioning
confidence: 74%
“…Since GWAS data show that the rs560887-G allele is associated with elevated FBG (Bouatia-Naji et al 2008; Chen et al 2008), the combination of these splicing (Baerenwald et al 2013) and G6pc2 KO mouse (Pound et al 2013; Wang et al 2007) studies suggest that rs560887 is a potentially causative variant. The association between G6PC2 and FBG has been confirmed in multiple GWAS and in different populations (Bouatia-Naji, et al 2009; Dupuis, et al 2010; Hu, et al 2009; Hu, et al 2010; Prokopenko, et al 2008; Reiling, et al 2009; Tam, et al 2010; Wang, et al 2013). …”
Section: Introductionmentioning
confidence: 74%
“…Genome-wide association studies have recently provided important new insights about the genetics of common forms of type 2 diabetes and some of its related quantitative traits such as FPG and HbA1c [6, 7, 1418, 3942]. The studies described here represent a key step in extending these discovery phase GWAS data through the analysis of the functional properties of variants that span the G6PC2 locus (ESM Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FPG and HbA1c are important metabolic traits that are correlated with the risk of developing type 2 diabetes [810] and cardiovascular-associated mortality [1113]. Multiple other studies have confirmed that the G6PC2 locus harbors the strongest common genetic determinant of FPG levels in terms of significance and effect size, particularly with a common single nucleotide polymorphism (SNP), rs560887, that is located in the third intron of G6PC2 , and that explains ~1% of the total variance in FPG [1418]. These genetic data are consistent with the ~15% decrease in FPG observed following a global knockout of G6pc2 in mice [4] and support the hypothesis that genetic variation within the G6PC2 gene, rather than surrounding genes, directly contribute to variations in FPG in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In stage 1, we recruited 1,892 unrelated type 2 diabetic patients from the inpatient database of Shanghai Diabetes Institute and 1,808 unrelated controls who had been recruited from the general population by the Shanghai Diabetes Studies [25,26]. In stage 2, we additionally recruited 1,663 type 2 diabetic patients from the Shanghai Diabetes Institute inpatient database and 1,408 controls from the general population in Shanghai.…”
Section: Methodsmentioning
confidence: 99%